Recent Publications (Quarterly Journal of Economics, 1969)
Recent Publications Get access The Quarterly Journal of Economics, Volume 83, Issue 4, November 1969, Page 706, https://doi.org/10.1093/qje/83.4.706 Published: 01 November 1969